2017
DOI: 10.1515/raon-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life assessed by the EORTC QLQ-C30 questionnaire in the general slovenian population

Abstract: BackgroundThe aim of our study was to obtain reference data of the EORTC QLQ-C30 quality of life dimensions for the general Slovenian population. We intend to provide the researchers and clinicians in our country with the expected mean health-related quality of life (HRQL) scores for distinctive socio-demographic population groups.MethodsThe EORTC QLQ-C30 questionnaire supplemented by a socio-demographic inquiry was mailed or distributed to 1,685 randomly selected individuals in the Slovenian population aged 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 20 publications
6
43
2
Order By: Relevance
“…Older participants experienced a deterioration for most of the functional scales, except for Emotional Functioning which was slightly increased in older people, and Social Functioning which was found to be unrelated to age. These findings are in line with earlier studies in general populations from other European countries .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Older participants experienced a deterioration for most of the functional scales, except for Emotional Functioning which was slightly increased in older people, and Social Functioning which was found to be unrelated to age. These findings are in line with earlier studies in general populations from other European countries .…”
Section: Discussionsupporting
confidence: 93%
“…It is important to recognize that people with bladder cancer may have a different baseline HRQoL compared with the general population, as the disease may have already had an impact at or around the time of diagnosis. No reference data are available for the general population in the UK; however, the mean scores of HRQoL (QLQ-C30) for the present study population were lower than data for the general populations of Germany, Norway, Sweden and Slovenia [30][31][32][33], but higher than the general population of the USA [34]. It is therefore, possible that HRQoL reference values for patients with bladder cancer depend on cultural factors; for example, Scandinavian populations have a high standard of living [35].…”
Section: Discussionmentioning
confidence: 99%
“…Hinz et al examined the use of the EORTC QLQ-C30 in the general German population in 2011, finding that the older populations had a significantly lower global health score than younger populations [ 21 ]. A study by Velenik et al examining HRQL measures in the EORTC QLQ-C30 in the general Slovenian population found that scores were significantly affected by gender, age, and social class; mean scores decreased with increasing age [ 22 ]. Comparing our results in Dutch prostate cancer survivors to these reference values of normative populations, age was a significant factor leading to decreased physical functioning.…”
Section: Discussionmentioning
confidence: 99%
“…For the comparison of QLQ-C30 scores with cancer-patient data, the EORTC QLG has published reference values generated for various cancer populations [15]. In addition, general population norm data have been collected in different countries over the last two decades, with European data available for Denmark [16,17], Germany [18e20], the Netherlands [21,22], Norway [23,24], Slovenia [25] and Sweden [26,27], with the latest German publication providing a European norm by collating data from different samples [20]. However, a major drawback of this work is that inter-country comparisons are hampered because of the lack of a common sampling methodology across studies.…”
Section: Introductionmentioning
confidence: 99%